Household's incomes 1975 - Statistics Sweden (Statistics Sweden, 1988)
The households´ incomes is a yearly survey of about 10.000 households´ economy based on data from a questionnaire, taxation registers and other official registers. 1975 was the first year the rotated sample method was used. Half the sample became part of the 1976 study. The purpose of this is to make better estimates of changes in income between succeeding years. This year was also the first where a longitudinal method was used. Starting every fifth year the income-changes will be followed up during a ten-year period. The purpose of this is to be able to answer questions about income-changes and income stability over longer periods. To be able to manage these changes in the study-design, a transition was made in 1975 from household sampling to individual sampling. The study is divided into four separate files and they contain information about sampling, work: weeks/year, hours/week, full-time work, occupation, sickness benefits, study benefits, social security, assessment data, family allowance, demography, socioeconomy, number and age of children, type of household, occupation variables, income variables, properties, business and discretionary assessment.

The households´ incomes is a yearly survey of about 10.000 households´ economy based on data from a questionnaire, taxation registers and other official registers. 1975 was the first year the rotated sample method was used. Half the sample became part of the 1976 study. The purpose of this is to make better estimates of changes in income between succeeding years. This year was also the first where a longitudinal method was used. Starting every fifth year the income-changes will be followed up during a ten-year period. The purpose of this is to be able to answer questions about income-changes and income stability over longer periods. To be able to manage these changes in the study-design, a transition was made in 1975 from household sampling to individual sampling. The study is divided into four separate files and they contain information about sampling, work: weeks/year, hours/week, full-time work, occupation, sickness benefits, study benefits, social security, assessment data, family allowance, demography, socioeconomy, number and age of children, type of household, occupation variables, income variables, properties, business and discretionary assessment.
Hushållens inkomster 1975
HINK75
Keywords: Economic conditions and indicators; Ekonomiska förhållanden och indikatorer; Income, property and investment/saving; Inkomster, egendom och investeringar/sparande; Employment; Sysselsättning; Social Sciences; Samhällsvetenskap